2017
DOI: 10.1111/jcmm.13296
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin‐mediated preservation of endothelial progenitor cell function via augmenting autophagy enhances ischaemic angiogenesis in diabetes

Abstract: Recently, the dipeptidyl peptidase‐4 (DPP‐4) inhibitor sitagliptin, a major anti‐hyperglycaemic agent, has received substantial attention as a therapeutic target for cardiovascular diseases via enhancing the number of circulating endothelial progenitor cells (EPCs). However, the direct effects of sitagliptin on EPC function remain elusive. In this study, we evaluated the proangiogenic effects of sitagliptin on a diabetic hind limb ischaemia (HLI) model in vivo and on EPC culture in vitro. Treatment of db/db mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Studies have also reported that HG contributes to autophagy in retinal cells and placenta . However, HG has also been shown to impair autophagy in endothelial progenitor cells and umbilical vein endothelial cells . These different results indicate that modulation of autophagy is complex and possibly dependent on the tissues and the pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that HG contributes to autophagy in retinal cells and placenta . However, HG has also been shown to impair autophagy in endothelial progenitor cells and umbilical vein endothelial cells . These different results indicate that modulation of autophagy is complex and possibly dependent on the tissues and the pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies have shown that the activation of autophagy under hypoxic conditions can stimulate VEGF expression to some extent (29), (30), (31) ,, it has remained unclear how autophagy upregulates HIF-1α to promote VEGF secretion. SIRT1 expression is known to be regulated by several transcription factors, microRNAs, and posttranscriptional modi cations; including sumoylation, ubiquitylation, and deubiquitylation.…”
Section: Discussionmentioning
confidence: 98%
“…Remm et al identified gliptin‐mediated endothelial regeneration proceeds through SDF‐1/CXCR4 in a GLP1R‐independent manner after acute vascular injury. Moreover, sitagliptin treatment could promote autophagy level, which played protective effects on functions of both EPCs and endothelial cells . However, the effect of sitagliptin on autophagy in MSCs cells was distinct.…”
Section: Mechanisms Involved In Cardiovascular Protection Of Sitagliptinmentioning
confidence: 94%